"A home away from hem": exploring and assessing hotel staycation as the new normal in the Covid-19 era. Issue 4 (28th January 2022) - Yan, Qi; Shen, Huawen; Hu, Yunhong
Abstract : Purpose: Enlightened by the theoretical framework of adapted protection motivation, this study aims to explore and assess the viability and resilience of hospitality consumption in the ongoing Covid-19 era as embodied in the activity of staycation, which is gaining popularity as a rare escape from the hemming in of the pandemic. Design/methodology/approach: This study collects data from staycation guests in Hong Kong, which at the time was under semi-lockdown imposing compulsory quarantine for inbound visitors. The data was analyzed through structural equation modeling (SEM). Findings: It is revealed by the study results that staycation experiences in Hong Kong are underpinned by a full mediating effect between place attachment and experience quality is performed by sense of presence, together with consolidation of experience quality and psychological detachment as tenable mediators in the research model. Aside from the utilitarian and hedonic values, hospitality and tourism consumption have been engrained with profound socio-cultural implications congenial to the collective identities, recollection and contemplation of a civilized society, with the Covid-19 era and the foreseeable future expected to be no exception. Practical implications: The results of this study can serve as reference regarding better planning and development of the staycation product as effective responses against the grave repercussions of the Covid-19 pandemic by hotel and hospitality practitioners and destination marketers and managers at large. In particular, the pandemic has inadvertently availed the opportunity for the destinationalization of the hotel and hospitality sector, with rich implications for industrial consolidations and coordination with destination authorities. Originality/value: The holistic structural research model derived and empirically examined entails major antecedents and consequences of the experience quality of staycation guests in locked-down Hong Kong, with the incorporation of the variables of place attachment and extended conceptualization of sense of presence accounting for the efficacy factors of the staycation takers in terms of locality and recollection appraisals, respectively. This study enriches theoretical articulations on staycation as the new normal of hospitality consumption in the lingering pandemic era.